Compliance and Subjective Patient Responses to Eyelid Hygiene. Issue 4 (July 2017) - Alghamdi, Yousef A.; Camp, Andrew; Feuer, William; Karp, Carol L.; Wellik, Sarah; Galor, Anat
Abstract : Objectives: Lid hygiene is a commonly prescribed first-line therapy in patients with lid margin disease, yet compliance with therapy is not well characterized. The goals of this study were to assess patient compliance with lid hygiene and evaluate which factors predict a favorable symptomatic response to treatment. Methods: This was a cross-sectional study of patients seen in the Miami Veterans Affairs eye clinic between August and December 2014. An evaluation was performed to assess dry eye symptoms and lid margin signs. All patients were then instructed to perform warm compresses and lid scrubs. A follow-up phone survey assessed compliance and subjective therapeutic response 6 weeks later. Results: Two hundred seven of 211 (98%) patients (94% male, 60% white) completed the survey. Of the 207 patients, 188 (91%) completed the follow-up survey. Compliance with therapy was reported in 104 patients (55%); 66 reported complete improvement, 30 partial improvement, and 8 no improvement in symptoms. Patients who self-reported dry eye symptoms at first visit (n=86, 74%) were more likely to be compliant with lid hygiene than those who did not report symptoms (n=18, 25%) ( P <0.0005). The only factor associated with poorer response to lid hygiene was longer time of self-reported dry eye symptoms. None of the other signs studied, including the presence of skin rosacea and lid margin telangiectasia, were associated with a differential response to lid hygiene. Conclusions: Patients with dry eye symptoms were moderately compliant with lid hygiene, and patients who performed the routine noted improvement in symptoms.